A piece of my heart - Sala, Sharon (Sala, Sharon. Blessings, Georgia series, 2017)
Mercy Dane, jaded from her past in a troubled foster home, races to Blessings, Georgia to donate blood to save the life of an accident victim, and is surprised when the grateful town opens its arms to her. Police Chief Lon Pittman finds himself drawn to her, and ready to do anything to convince her that home is where their heart is.